The appropriateness of the financial and banking department curriculum with the requirements of financial institutions - accounting approach Comparative and field study in the Kurdistan Region - Iraq - المدرس المساعد فیصل نجم الدین عبداه; المدرس الدکتور نسيم يوسف حنا (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The basic skills for a student during university study are the base to start field work. By this concept, the study measures how the curricula of banking and financial department are convenient with labor market requirements into financial institutes. The study concentrates on the contrast of differences between curricula of banking and financial department and departments of business and administration, economic and accounting in college of administration and economics in Salahadin university of Erbil. The results show convergence of curricula of department of Finance and Banking and accounting department. The researcher studied as well the accounting professional skills of accounting department graduates in contrast with banking and financial department graduates. The results of the study confirm the researcher’s achievements of curricula study. Thus, a review of curriculum is needed in the banking and financial department as a question is raised on how much a student has benefit of four years studying to be prepared at least to be responsible as a graduate of banking and financial department in consideration of the current curricula applied.